Given a function f defined as f ( x ) = 2 x + 1 , find the value of
n → ∞ lim 2 2 n + 1 ( 1 − f n ( − 1 ) ) .
Details and Assumptions
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I too have done via same way..
I want to ask that why did you take x = cos 2 θ ? The value of x can be any real number greater than − 1 but taking x = c o s 2 θ limits its value. Am i going wrong somewhere. If so please explain @Hargun Singh
just put x=cos (a) , this is a standard question in almost all textbooks ,,
Honestly speaking it is a standard question in alomst all textbooks, but
I made the question myself.
You are exactly right.
I just do math for fun, I'm only 15 and im running out of math problems to do. Can you make more math problems.
Problem Loading...
Note Loading...
Set Loading...
Substitute x = cos 2 θ , θ ∈ [ 0 , π / 2 ]
After doing so, we get
f ( x ) = f ( cos 2 θ ) = cos θ
f 2 ( x ) = f ( cos θ ) = cos 2 θ
⋮
f n ( x ) = cos 2 n − 1 θ
So, the required limit
L = n → ∞ lim 2 2 n + 1 ( 1 − f n ( x ) ) = n → ∞ lim 2 . 2 2 n ( 1 − cos 2 n − 1 θ ) = n → ∞ lim 4 . 2 2 n sin 2 2 n θ = 4 θ 2 = ( cos − 1 x ) 2
Plugging in x = − 1 , we get L = π 2 .